The Effect of Profit Precision Dimensions On board of Director’s Bonus in Companies Listed in Tehran Stock Exchange - Sayed Ali Vaez (Ph.D) (Shahid Bahonar University of Kerman, 2018)
If the reward is not commensurate with managers actual performance not only increase corporate value but also is a means to transfer wealth. In this study, the question is raised that, Is in the reward programs to Motivation to achieve Profit threshold and Asymmetric adjustments of profit target, that effect the precision of earnings in form of manipulation and management them, attention and attention is enough? So the main aim of our study was to evaluate the effect of Motivation to achieve Profit threshold and Asymmetric adjustments of profit target as a dimension of precision of earnings, to board of director’s bonus. Therefore, the data related to the companies listed in Tehran Stock Exchange for the period 2009 to 2016 were extracted and the combination regression model were used to test the hypothesis. The results show that the Achieving profit thresholds, played an active role in rewarding managers, And they reduce the bonus and asymmetric adjustment of target profits will have a positive effect on bonus, while in companies with good and poor performance in the industry, this has a negative and significant impact on bonus.